The Relatıonshıp Of The Nsar Angle Wıth Sna, Sn, Snd Angles In Adults Of Normal Occlusıon - Emel Seren (Turkish Journal of Orthodontics, 1990)

(untitled)
The mean values of NSAr = S, SNA, SNB and SND, their standart deviations and the difference between the sexes were evaluated statistically by cephalometric measurements among 53 adult (24 females and 29 males) with normal dental and skeletal occlusion. When the relation benveen angle S, with SNA, SNB and SND angles was examined; it was found out that there was a significant negative relation and a parellelism in correlation. The negative relationship of these angles has proved that there is an accomodation between the middle cranial region and the jaws.